Folic Acid Modified Graphene Quantum Dots from Konjac Glucomannan for Cell Imaging and Targeted Drug Delivery. Issue 46 (8th December 2022) - Kang, Huiting; Wang, Tengfei; Liu, Wei; Tian, Dating
Abstract: Green and low‐cost photoluminescent graphene quantum dots (GQDs) were prepared by a one‐step hydrothermal method with konjac glucomannan (KGM), a natural polysaccharide, as the precursors. Then, the folic acid (FA)‐functionalized GQDs (FA‐GQDs) was formed by the amidation of GQDs with FA, and the drug carrier named as FA‐GQDs‐DOX was obtained by loading doxorubicin (DOX) on FA‐GQDs. Due to the inherent fluorescence properties of GQDs and DOX in FA‐GQDs‐DOX, the resultant samples could be used to selectively label cancer cells without external dyes, and the cellular uptake and the drug‐releasing behavior could be visualized. The coupling of FA with GQDs and the loading of DOX on FA‐GQDs were confirmed by various means. In addition, the cell imaging showed that the FA‐GQDs could be used as a fluorescent probe to recognize folate receptor (FR)‐positive cancer cells and that the FA‐GQDs‐DOX could selectively deliver DOX to FR‐positive cancer cells. As a result, the FA‐GQDs‐DOX could be applied in early diagnosis and targeted therapy of cancer. Abstract : Folic acid (FA)‐functionalized GQDs (FA‐GQDs) prepared by the amidation of GQDs with FA and conjugated with doxorubicin (DOX). The cell imaging and target drug delivery of the sample were evaluated. The results indicated that the obtained sample was a promising candidate for the early diagnosis and targeted therapy of cancer.